Агапій Шамрай у пошуках синтетичної теорії літератури: 1920-ті роки - Бабак, Г. (Слово і Час, 2022)
У статті розглянуто теоретичні погляди літературознавця Агапія
Шамрая (1896—1952) у контексті рецепції філологічної системи О. Потебні та розвитку формального й соціологічного методів в українському
літературознавстві та критиці 1920-х років. Окрему увагу приділено
вивченню проблеми читача як спробі поєднати два підходи до розуміння
літературного твору — формальний і соціологічний. У статті також
порушено проблему «синтетичності» українського літературознавства 1920-х. This article reconstructs the theoretical views of a literary historian and critic Ahapii Pylypovych
Shamrai (1896—1952) in the context of perception of Oleksandr Potebnia’s philological
and linguistic heritage — and at the same time in the context of the development of
the formal method and sociological approach in Ukrainian literary criticism in the 1920s.
The study offers a detailed analysis of Shamrai’s early work “O. Potebnia and the methodology
of the history of literature” (1924) in the connection with Russian formalists’ critical
approach to Potebnia’s theoretical ideas. In his early work, Shamrai calls for a rethinking
of Potebnia’s theory of the ‘inner form of the word’ and some of his other ideas, which, in
his opinion, could be the basement for the further development of Ukrainian and Russian
literary theory. Particular attention is paid to the study of a reader (audience) as a major
component of literary analysis and interpretation. The idea of ‘studying a reader’ was crucial
when Ukrainian scholars tried to combine two theoretical approaches — the formal and
sociological methods. One of the best examples of such ‘synthetism’ in Ukrainian literary
studies of the 1920s was Shamrai’s textbook “Ukrainian Literature. Brief overview” (1927,
1928), which is discussed in this article. The paper also argues that “synthetism” was inherent
to the Ukrainian literary criticism of the 1920s in general. It was a theoretical framework
used by many Ukrainian literary scholars, Oleksandr Biletskyi and Borys Jakubskyi being
among them. Providing a historical context for Shamrai’s theories, the article also examines
the historical and philological ideas of his older contemporary Oleksandr Biletskyi and estimates
their influence on the development of Ukrainian literary criticism of that time.